The flexibility and adaptation strategy of local filmmakers amid the pandemic: Opportunity and threat - Suwarto, Dyna Herlina; Kulau, Febriansyah (2022)
The COVID-19 pandemic disturbed the local film industry heavily since most of the film projects were delayed or cancelled. Despite the fragile situation, local filmmakers adopted flexible and adaptive strategies to survive. The flexible strategies related to fighting (the alternative jobs, project switch) and freezing (work from home). After three months, all film practitioners decided to fight for the new normal as they found job opportunities in social media content, corporate and government service, streaming platforms and film production. The screen industries supported the local filmmakers to survive. During the emergency period, the closed network was beneficial; nonetheless, they should expand their open network to adapt to a new normality. Apart from the resistance, filmmakers are continuously under precariousness, particularly about health threats and underpaid work. © 2022 Intellect Ltd Article.